A dynamical systems approach to modeling human development - Shyam Ranganathan; Ranjula Bali Swain; David J. T. Sumpter (Uppsala University, Department of Economics, 2014)
A key aim of economics is to set goals and investigate the relationship between various socio-economic indicators. By fitting time series data using a Bayesian dynamical systems approach we identify non-linear interactions between GDP, child mortality, fertility rate and female education. We show that reduction in child mortality is best predicted by the level of GDP in a country over the preceding 5 years. Fertility rate decreases when current or predicted child mortality is low, and is weakly dependent on female education and economic growth. As fertility drops, GDP increases producing a cycle that drives the demographic transition.
urn:nbn:se:uu:diva-235541
Keywords: C51; C52; C53; C61; J13; O21; 330; Demographic transition; Human Development; dynamical systems; Bayesian; data-driven; GDP; child mortality; fertility rate